A black–red phosphorus heterostructure for efficient visible-light-driven photocatalysis1. Issue 7 (21st February 2015) - Shen, Zhurui; Sun, Shoutian; Wang, Wanjun; Liu, Jianwen; Liu, Zhifeng; Yu, Jimmy C.
<x xml:space="preserve">Abstract</x> A new single elemental heterostructure of black–red phosphorus was prepared, which exhibited high visible-light-driven photocatalytic activity comparable to that of CdS.